Анна Каренина: роман в 8 частях / комментарии Э. Г. Бабаева] - Толстой Лев Николаевич (1981)
Экземпляры: Селтинская районная библиотека (к/х) (20200605) / Инвентарный номер: 36530 / Авт.знак: Т 53 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)